1954
DOI: 10.1037/h0063617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulus complexity on discrimination responses.

Abstract: Control systems utilizing visual displays require rapid, error-free responses on the part of the operator for optimum use. The responses depend on the detection of differences in the stimulus objects of the display. The present investigation provides information relative to the nature of the changes in proficiency of performance of discriminative responses to visual stimuli that vary in location, size, or intensity.Since visual displays usually incorporate more than one dimension of variation in them so that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

1964
1964
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 7 publications
3
27
1
Order By: Relevance
“…That is to say, Hick (1952) has pointed out that the rate of gain of information in choice reactions is a constant, and several other researchers have verified that disjunctive RT is indeed an increasing linear function of the amount of information transmitted in choice reactions (Crossman, 1953;Gregg, 1954). It is true that other researchers have found conditions under which RT has failed to increase with either uncertainty or the amount of information transmitted (Leonard, 1959;Mowbray & Rhoades, 1959;Mowbray, 1960), or under which various factors apparently influence the degree of increase (Brainard et al , 1962;Fitts & Switzer, 1962), but these negative cases appear to have been explained as stimulus-response compatibility effects (Alluisi et at;Alluisi, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, Hick (1952) has pointed out that the rate of gain of information in choice reactions is a constant, and several other researchers have verified that disjunctive RT is indeed an increasing linear function of the amount of information transmitted in choice reactions (Crossman, 1953;Gregg, 1954). It is true that other researchers have found conditions under which RT has failed to increase with either uncertainty or the amount of information transmitted (Leonard, 1959;Mowbray & Rhoades, 1959;Mowbray, 1960), or under which various factors apparently influence the degree of increase (Brainard et al , 1962;Fitts & Switzer, 1962), but these negative cases appear to have been explained as stimulus-response compatibility effects (Alluisi et at;Alluisi, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since Archer's (1954) task was easier than Gregg's (1954), there is a suggestion that the difficulty of the discrimination may also interact with the always-irrelevant type of irrelevant information.…”
Section: Analyses Of Errors Reaction Times and Rates Of Informationmentioning
confidence: 99%
“…The time required both for solving a conceptidentification problem (Archer et al , 1954) and for making visual (Gregg, 1954) and auditory (Montague, 1965) discriminations has been found to increase with increases in the amount of irrelevant information presented with the stimuli. On the other hand, the time required for making simple visual pattern discriminations has been found to be independent of the amount of irrelevant information presented (Archer, 1954).…”
Section: Analyses Of Errors Reaction Times and Rates Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Hick (1952) initially pointed out that the rate of gain of information is a constant, several researchers have found that disjunctive reaction time (RT) is an increasing linear function of the amount of information transmitted (Ht) per S-R event (e. g., Crossman, 1953;Gregg, 1954). Others, however, have found conditipns under which RT has failed to increase with either Ht or stimulus uncertainty (Leonard, 1959;Mowbray & Rhoades, 1959;Mowbray, 1960), or under which various factors apparently influence the degree of increase (Brainard et aI., 1962;Fitts & Switzer, 1962).…”
Section: Introductionmentioning
confidence: 99%